2019
DOI: 10.1021/acssensors.9b01244
|View full text |Cite
|
Sign up to set email alerts
|

An Innovative Modular eNose System Based on a Unique Combination of Analog and Digital Metal Oxide Sensors

Abstract: An innovative concept for an electronic nose (eNose) system based on a unique combination of analog and digital sensors for online monitoring is presented. The developed system consists of small sensing arrays of commercially available semiconducting metal oxide (MOX) gas sensors in a compact, modular, low sample volume, temperature-controlled sensing chamber. The sensing chamber comprises three compartments, each of which may contain several analog and/or digital MOX sensors. Additional sensors within the dig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 34 publications
(39 reference statements)
0
23
0
Order By: Relevance
“…Some researchers have used a selection of these sensors in devices for air quality monitoring purposes [22,23], but applications in breath research are limited. The breath E-nose developed by Jaeschke et al [24] uses many of the most relevant commercial gas sensors currently available. However, this unit focuses on a modular approach with three exchangeable sensing compartments and has not been tested using exhaled breath samples.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers have used a selection of these sensors in devices for air quality monitoring purposes [22,23], but applications in breath research are limited. The breath E-nose developed by Jaeschke et al [24] uses many of the most relevant commercial gas sensors currently available. However, this unit focuses on a modular approach with three exchangeable sensing compartments and has not been tested using exhaled breath samples.…”
Section: Introductionmentioning
confidence: 99%
“…The hold-out CV method was used to train the LDA model. The maximum 76.4% LDA accuracy was recorded for the classification of different VOC concentrations [132] (see Figure 14A). The lower accuracy rate might have been due to the inappropriate selection of the CV method since the hold-out method randomly shuffled the entire dataset for training and testing.…”
Section: Chemiresistive Type Smart Gas Sensors Using Machine Learningmentioning
confidence: 99%
“…Jaeschke et al [132] demonstrated an innovative e-nose system using a unique combination of analog and digital MOx sensors for ethanol and acetone detection in dry and humid environments. The sensing array consisted of 8 analog and 10 digital sensors.…”
Section: Chemiresistive Type Smart Gas Sensors Using Machine Learningmentioning
confidence: 99%
“…In this work, we explore the performance of several CT techniques in a real-life breath analysis study using our recently published [ 80 , 81 ] sensing array and three instruments. The experiment consists of the discrimination of breath samples from people before and after eating a specified meal.…”
Section: Introductionmentioning
confidence: 99%
“…This study is mainly motivated by the difficulty of calibration of eNoses for breath analysis applications, the differences between instruments, the frequent recalibrations needed due to aging and drift and the environmental and other different conditions present in different hospitals which prevents obtaining a unified dataset for deep statistical studies. Another goal in this work, is to present our modular breath analyzer (MBA) platform (shown in Figure 1 ), a new updated version of our modular eNose [ 80 , 81 , 82 ] specifically designed for breath analysis. The previous version of the modular eNose concept was recently presented [ 80 , 81 , 82 ].…”
Section: Introductionmentioning
confidence: 99%